Visible and infrared photoluminescence from erbium-doped silicon nanocrystals produced by rf sputtering - Cerqueira, M.F.
Erbium-doped low-dimensional Si films with different microstructures were deposited by reactive magnetron sputtering on glass substrates by varying the hydrogen flow rate during deposition. Amorphous, micro- and nanocrystalline samples, consisting of Si nanocrystalls embedded in silicon-based matrices with different structures, were achieved with optical properties in the visible and IR depending on nanocrystalline fraction and matrix structure and chemical composition. Structural characterization was performed by X-ray diffraction in the grazing incidence geometry and Raman spectroscopy. The chemical composition was studied using RBS/ERD techniques. Spectroscopic ellipsometry was combined with the previous techniques to further resolve the film microstructure and composition. In particular, the distribution along the film thickness of the volume fractions of nanocrystalline/amorphous silicon and SiOx phases has been obtained. In this contribution we discuss visible and infrared photoluminescence as a function of sample microstructure and of the oxygen/hydrogen concentration ratio present in the matrix.